The Relationship Between Job Stressors And Job Burnout Among Nurses: A Case Study At Metro Specialist Hospital / Khairul Naqwan Md Razip and Tuan Ahmad Fakhruddin Tuan Rosdi - Md Razip, Khairul Naqwan; Tuan Rosdi, Tuan Ahmad (2010)
This study made effort to examine the relationship between job stressors and job burnout among nurses at Metro Specialist Hospital. Among the helping professions, nurses are the largest group with the mission to nurture and care for people in the health/ illness experience. Services are provided by nurses in a variety of areas: hospitals, long-term care facilities, homes, and communities. Comfort, help, support, presence, and skilled services are provided when individuals are facing pain, loss, disease, death, and loneliness. Increasing number of patients by each year compare to the shortage of nurses faced by both government and private hospital and health care institution create higher workload and burdens for nurses to deal with. The burdens and work overload faced by nurses create job stress among them. There is a fatal or even chronic problem as the stress faced by those nurses will lead them to experience job burnout. The job burnout can be in form of emotional exhaustion, depersonalization and lack of personal accomplishment. The results gained by this research will be used to examine how strong the job stressors influenced job burnout and which job stressor that mostly influenced the job burnout. The results also will be used in order to make any appropriate recommendations to the management as the researchers' view the seriousness of the job burnout among nurses can be a fatal problem that need to be curb in making the health care institution become more productive and effective in serving the humanity.